The cephalic radiograph: beyond a cephalometric measure (2014)
Orthodontic practice recognizes the importance of the cephalic lateral radiograph, although it is actually limited to quan- titative analysis. A literature review was made to assess the morphological characteristics that, at first glance, can be evaluated in the radiography and constitute tools for predicting risk factors, prognosis, and stability. The conclusion is that the cephalic lateral radio- graph gives a broader view of craniofacial growth patterns, which can be modified by various structures such as skull base, cranio- cervical posture, airways, and position of the hyoid bone; this without losing sight of the cervical vertebrae and the morphology of the mandibular symphysis, which are important diagnostic factors when making clinical decisions. Cephalic lateral radiography therefore provides important qualitative information that cannot be ignored and which enables accurate diagnosis.